2013
DOI: 10.1111/1365-2745.12135
|View full text |Cite
|
Sign up to set email alerts
|

Pollen assemblage richness does not reflect regional plant species richness: a cautionary tale

Abstract: Summary1. Palaeoecological records of species richness spanning time intervals over which climate variables have shifted relative to one another can help reduce issues of colinearity that might affect our understanding of patterns of species richness.2. Fossil pollen assemblages have the potential to serve as a proxy for past plant richness because they record the presence of plant taxa. However, pollen assemblages are typically limited by low taxonomic resolution and taphonomic processes (pollen production, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 42 publications
0
64
1
3
Order By: Relevance
“…However, comparison of richness between high diversity (tropical) and low diversity (temperate) systems does seem to demonstrate that pollen richness does track vegetation diversity at a global scale. The range of palynological richness captured in the tropical traps presented here is 86-144 pollen types (Table 1), compared with richness values from temperate regions which are typically lower; for example 3-27 pollen types in > 500 modern lake samples in North America (Goring et al 2013), and 9-45 pollen types in fossil records from a wide variety of temperate regions across the globe (Flenley 2005).…”
Section: Tropical Pollen and Vegetation Richnessmentioning
confidence: 88%
See 2 more Smart Citations
“…However, comparison of richness between high diversity (tropical) and low diversity (temperate) systems does seem to demonstrate that pollen richness does track vegetation diversity at a global scale. The range of palynological richness captured in the tropical traps presented here is 86-144 pollen types (Table 1), compared with richness values from temperate regions which are typically lower; for example 3-27 pollen types in > 500 modern lake samples in North America (Goring et al 2013), and 9-45 pollen types in fossil records from a wide variety of temperate regions across the globe (Flenley 2005).…”
Section: Tropical Pollen and Vegetation Richnessmentioning
confidence: 88%
“…The absence of a clear relationship between the pollen and vegetation richness (Fig. 1b) suggests that, perhaps unsurprisingly, factors other than the plot (local) vegetation richness are playing an important role in determining palynological richness (Goring et al 2013;Birks et al 2016). Important factors likely to be influencing the pollen rain, and consequently the richness signal, are variations in flower structure and pollen dispersal mechanism (Bush 1995;Bush andRivera 1998, 2001).…”
Section: Tropical Pollen and Vegetation Richnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as macrofossils are random parts of the whole organism, diversity estimation is always problematic. Some studies have shown that pollen diversity and vegetation diversity do not coincide (Goring et al, 2013), while others show that their trends can be consistent, and it may be possible to derive community diversity changes in time from fossil diversity tendencies (van der Knaap, 2009). Diversity estimation using transfer functions has been rarely attempted and might be potentially useful.…”
Section: Abundance and Diversitymentioning
confidence: 99%
“…El tamaño de los restos y su resistencia a la descomposición y la idoneidad de los depósitos sedimentarios para conservar material orgánico (temperatura, pH y falta de oxígeno) limitan el proceso de fosilización. Asimismo los procesos tafonómicos (incluyendo la producción, el transporte y su deposición) limitan la correspondencia entre el registro fósil y la vegetación en el pasado (Goring et al, 2013). Por ello, el registro fósil está sesgado hacia determinados taxones, períodos de tiempo y sitios que contienen aquellas condiciones favorables para su preservación (Behrensmeyer et al, 2000y Varela et al, 2011.…”
Section:  Calibración De Los Modelos De Distribución De Especiesunclassified